Action of anti-bothropic factor isolated from Didelphis marsupialis on renal effects of Bothrops erythromelas venom - Martins, Alice M.C.; Sousa, Fabiola C.M.; Barbosa, Paulo S.F.; Toyama, Marcos H. [UNESP]; Toyama, Daniela O.; Aprígio, Cleidiana C.; Queiroz, Maria G.R.; Guarnieri, Mirian C.; Havt, Alexandre; De Menezes, Dalgimar B.; Fonteles, Manassés C.; Monteiro, Helena S.A. (Elsevier, 2005)
Acute renal failure is the most common complication in the lethal cases caused by snakebites in Brazil. Among the Brazilian venom snakes, Bothrops erythromelas is responsible for the majority of accidents in Northeastern Brazil. Didelphis marsupialis serum could inhibit myonecrotic, hemorrhagic, edematogenic hyperalgesic and lethal effects of envenomation determined by ophidian bites. In the present study, we evaluated the action of the anti-bothropic factor isolated from D. marsupialis on the renal effects promoted by B. erythromelas venom without systemic interference. Isolated kidneys from Wistar rats were perfused with Krebs-Henseleit solution containing 6% bovine serum albumin. We analyzed renal perfusion pressure (PP), renal vascular resistance (RVR), glomerular filtration rate (GFR), urinary flow (UF), and the percentages of sodium and potassium tubular transport (%TNa +, %TK +). The B. erythromelas venom (10 μg mL -1) decreased the PP (ct=108.71±5.09 mmHg; BE=65.21±5.6 mmHg*) and RVR (ct=5.76±0.65 mmHg mL -1 g -1 min -1; BE=3.10±0.45 mmHg mL -1 g -1 min -1*) . On the other hand, the GFR decreased at 60 min (ct 60=0.76±0. 07 mL g -1 min -1; BE 60=0.42±0.12 mL g -1 min -1*) and increased at 120 min (ct 120=0.72±0.01 mL g -1 min -1; BE 120=1.24±0.26 mL g -1 min -1*). The UF increased significantly when compared with the control group (ct=0.14±0.01 mL g -1 min -1; BE=0.47±0.08 mL g -1 min -1*). The venom reduced the %TNa + (ct 90=79.18±0.88%; BE 90=58.35±4.86%*) and %TK + (ct 90=67.20±4.04%; BE 90=57. 32±5.26%*) The anti-bothropic factor from D. marsupialis (10 μg mL -1) incubated with B. erythromelas venom (10 μg mL -1) blocked the effects on PP, RVR, %TNa +, and %TK +, but was not able to reverse the effects in UF and GFR promoted by venom alone. However, the highest concentration of D. marsupialis serum (30 μg mL -1) reversed all the renal effects induced by the venom. In conclusion, B. erythromelas venom altered all the renal functional parameters evaluated and the anti-bothropic factor from D. marsupialis was able to inhibit the effects induced by the venom in isolated kidney. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Anti-bothropic factor; Bothrops erytromrlas; Renal effects; bothropic factor antibody; bovine serum albumin; snake venom; unclassified drug; venom antiserum; animal experiment; animal tissue; comparative study; concentration (parameters); controlled study; drug isolation; drug mechanism; drug screening; female; glomerulus filtration rate; kidney; kidney perfusion; kidney vascular resistance; male; nonhuman; opossum; perfusion pressure; potassium transport; priority journal; rat; snake; sodium transport; statistical significance; urine flow rate; Animals; Bothrops; Brazil; Carrier Proteins; Crotalid Venoms; Didelphis; Glomerular Filtration Rate; Kidney; Perfusion; Potassium; Rats; Rats, Wistar; Sodium; Vascular Resistance; Bothrops erythromelas; Bovinae; Didelphis marsupialis; Rattus norvegicus; Serpentes